2017
DOI: 10.1002/rcs.1856
|View full text |Cite
|
Sign up to set email alerts
|

Single‐incision robotic cholecystectomy is associated with a high rate of trocar‐site infection

Abstract: The robotic approach does not seem to offer additional benefit in terms of surgical outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Higher hernia rates after SSRC than LC can be explained by a wider incision along the linea alba to insert the single‐site port. The further enlargement of the mini‐laparotomy at the end of the procedure is probably due to excessive force of the robotic system at the incision site 16 . A wide abdominal access may be considered an advantage in case of big gallbladder stones (>1.5 cm), but at the same time it may be linked to a higher risk of hernia development.…”
Section: Discussionmentioning
confidence: 99%
“…Higher hernia rates after SSRC than LC can be explained by a wider incision along the linea alba to insert the single‐site port. The further enlargement of the mini‐laparotomy at the end of the procedure is probably due to excessive force of the robotic system at the incision site 16 . A wide abdominal access may be considered an advantage in case of big gallbladder stones (>1.5 cm), but at the same time it may be linked to a higher risk of hernia development.…”
Section: Discussionmentioning
confidence: 99%
“…The exclusion was due to several reasons, including not having control groups, multiport laparoscopic, and pediatric populations. Hence, a final 13 studies (of 817 and 757 patients who underwent SSRC and SILC) were included for quantitative synthesis 13–25 . One study was a single‐blind RCT, nine were retrospective cohorts, and the remaining three were prospective cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, a final 13 studies (of 817 and 757 patients who underwent SSRC and SILC) were included for quantitative synthesis. [13][14][15][16][17][18][19][20][21][22][23][24][25] One study was a single-blind RCT, nine were retrospective cohorts, and the remaining three were prospective cohort studies. The data characteristics are available in Table 1.…”
Section: Study Selection and Study Characteristicsmentioning
confidence: 99%
“…Minimally invasive surgery for gallbladder disease has advantages of less pain, smaller scars, shorter length of hospital stay and quicker return to normal activities, which has become increasingly popular in patients (Bignell et al 2013;Bisgaard et al 2002;Sinagra et al 2018). Although several studies have revealed the e cacy of SILC, its increased risks of pain, bile duct injury and port-site hernia formation with a larger umbilical incision and prolonged operative time, and the need for specialty ports and instruments have raised con icting concerns (Arezzo et al 2018;Hoyuela et al 2019;Lee et al 2019;Lim et al 2017). In this study, a TILC technique was described that only needs conventional instruments.…”
Section: Discussionmentioning
confidence: 99%